PERSEPSI MAHASISWA AKUNTANSI PADA PERILAKU WHISTLEBLOWING - Lasmini, Ni Nengah; Ramantha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
Consistent and repeated of financial frauds have given serious adverse effect on whole business sector. Whistleblowing is one of the most effective solution for detecting financial frauds, but most people still avoiding be a whistleblower because of many factors can affecting, so that this research aimed to explain and explore factors that affecting whistleblowing behaviour. This research take place at Faculty of Economic and Business Udayana University with total sample 321 accounting students in bachelor degree and master degree. Data analyse using structural analysis by SmartPLS 3.2.6 64bit software program through evaluating outer model, inner model and hypothesis testing. This research shows: first whistleblowing intention mediating effect of attitude toward behavior on whistleblowing behavior. Second, subjective norm just having positive effect on whistleblowing intention but fail to mediate effect subjective norm on whistleblowing behavior.  Third, whistleblowing intention mediating effect perceived behavior control on whistleblowing behavior. Fourth, perceived behavior control has positive effect on whistleblowing behavior